Dilemma of Legal Policy to Address Cybercrime in the Digital Era - Erikha, Annisa; Saptomo, Ade (Pelopor Publikasi Akademika, 2024)
Addressing cybercrime in Indonesia faces various complex challenges, including legal vacuums in existing regulations, such as the Law on Information and Electronic Transactions (UU ITE) and personal data protection. This study examines the necessity of regulatory reform that is more adaptive to the development of new technologies such as artificial intelligence, blockchain, and cryptocurrency, as well as the importance of balancing individual privacy protection and the data access needs of law enforcement. Furthermore, this research highlights the role of international collaboration in tackling cross-border cybercrime, which necessitates regulatory harmonization and extradition agreements to enhance the effectiveness of law enforcement. Through a comprehensive approach that includes legal reform, the implementation of stringent personal data protection, and strengthened international cooperation, Indonesia can create a safe and protected digital environment from the threats of cybercrime.